‘Where all my bad girls at?’: cosmopolitan femininity through racialised appropriations in K-pop - Garza, Joyhanna Yoo (Gender and Language, 2021)
This article examines the polyvalence of racial(ised) representations in K-pop performances. The analysis of K-pop star CL’s (2013) song and video ‘Nappeun gijibae’ (‘The bad girl’) demonstrates how the artist projects an assertive femininity by embodying and localising the Bad Bitch: a sexually agentive figure of womanhood from US hip hop. CL’s use of African American English and conventionalised hip hop tropes helps resignify gijibae, a pejorative Korean term for women. By shifting between decontextualised styles invoking a different time and place, CL is able to build a kind of chronotopic capital that transforms fragmented styles into an empowered cosmopolitan femininity. However, although CL’s performance challenges Korean gendered norms in its use of local linguistic resources, her selective appropriations of US Black and Chicanx cultural signifiers reproduce narrow images of racialised femininities and reify a hierarchy of valuation along lines of gender and race.
Keywords: 2000 à aujourd'hui; K-pop; approches et analyses; appropriation culturelle; asie; chronotope; corps; corée du sud; cours; discipline; féminisme pop; lin2685; linguistique; performance de genre; premier cycle; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques

"You Can Never Be Too Rich or Too Thin": Popular and Consumer Culture and the Americanization of Asian American Girls and Young Women - Lee, Stacey J.; Vaught, Sabina (The Journal of Negro Education, 2003)
First- and second-generation youth of color are vulnerable to racialized images of gender and sexuality as reflected in and perpetuated by dominant forms of popular and consumer cultures. These popular images inform the process of Americanization, including racialized sexualization, for first- and second-generation Americans. This paper examines the way first- and second-generation Asian American girls and young women interpret and reinterpret popular representations of their positions in the United States. Data from two qualitative studies on Asian American young women will be presented.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; corps; cours; discipline; féminisme pop; hmong; intersectionnalité; laos; premier cycle; périodes historiques; racisme; représentation des femme*; représentation des femmes* racisées; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis